Bilateral Temporal Bone Fractures with Bilateral Facial Nerve Palsy - Sabarigirish, Kanjully; BR, Lohith; Saxena, Sanjeev; Swami, Himanshu; Dutta, Angshuman (Indian Journal of Neurotrauma, 2016)
Bilateral fracture of the temporal bone is a rare cause of bilateral symmetrical simultaneous facial nerve palsy. Early clinical diagnosis of bilateral facial palsy is often delayed due to poor neurologic status of the patient and the absence of asymmetry of the face. Lack of comparison with an unaffected side further compounds assessment of severity with electroneuronography. We report a case of a 27-year-old with bilateral facial nerve palsy following a traumatic head injury causing symmetrical longitudinal fractures of both petrous temporal bones. Follow-up 6 months after facial nerve grafting on the right side and decompression on the left side showed early recovery on both sides.
Keywords: bilateral facial palsy; fracture; temporal bone